2014
DOI: 10.4103/0300-1652.137190
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptom, lung function and exhaled carbon monoxide among a sample of traffic workers in Lagos, Nigeria: A pilot survey

Abstract: Background:Traffic-related air pollution (TRAP) is a major source of air pollution but the impact on health in Nigeria is not well described.Patients and Methods:A descriptive cross-sectional study of road traffic workers and university students in Lagos. Eligible, accessible and willing participants were included in the sample. Respiratory symptoms and anthropometry were obtained from all the participants using an adapted Medical Research Council (MRC) questionnaire and they all did a spirometry test and exha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
(22 reference statements)
1
9
1
1
Order By: Relevance
“…The prevalence of allergic rhinitis in this study is high compared to that reported in Bogota (26.1%) in traffic police [26] and in a study done in Benin [27] among residents near busy roads with a prevalence of allergic rhinitis of 35.7%. Studies have shown higher prevalence of allergic rhinitis than those found in our study in workers with high exposure to outdoor air pollution in Nigeria (48.9%) [28] and Italy (48.5%) [29]. Consistent with previous studies, the prevalence of allergic rhinitis decreases with age [6] [30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of allergic rhinitis in this study is high compared to that reported in Bogota (26.1%) in traffic police [26] and in a study done in Benin [27] among residents near busy roads with a prevalence of allergic rhinitis of 35.7%. Studies have shown higher prevalence of allergic rhinitis than those found in our study in workers with high exposure to outdoor air pollution in Nigeria (48.9%) [28] and Italy (48.5%) [29]. Consistent with previous studies, the prevalence of allergic rhinitis decreases with age [6] [30].…”
Section: Discussionsupporting
confidence: 91%
“…Vendors who had a long daily working time, had a higher prevalence of allergic rhinitis. This is due to the duration of exposure to air pollutants as shown by the study by Obaseki et al, 2014 [28]. Some studies showed that BMI is associated with the prevalence of allergic rhinitis.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, the prevalence of diagnosed allergy in traffic warders (almost 50%) was statistically higher than in non-exposed office employers. Before us, Proietti et al found no statistically significant association between occupational exposure and diagnosis of allergic diseases [67], while Gao et al highlighted only a greater risk of allergic-related respiratory symptoms [68]. Regarding the latter, our analysis found no difference in pulmonary function between the exposed and control groups.…”
Section: Discussioncontrasting
confidence: 56%
“…However, most studies of workers exposed to traffic air pollution have been made in traffic police because of their high exposure to this pollution. In the traffic police in Nigeria, a high prevalence of respiratory symptoms was also found [14]. A predominance of respiratory symptoms has been found in bus drivers working in the HLM neighborhood.…”
Section: Discussionmentioning
confidence: 93%